The roles and importance of MICE destination attributes on the formation of host destination image - Lim, Khong Chiu; Ananzeh, Omar A. (2012)
The image of the destination has a significant role on tourists' travel decision and selection of destination to visit.Numerous studies have been conducted to examine and explore the agents that form the touristic image of the destinations.This study examines the role of MICE destination attributes on the formation of the touristic image of Jordan from the perspective of local and international MICE event participants.A total of 857 self-administered questionnaires of MICE event participants at 12 selected events were analyzed.The results revealed that MICE destination attributes influence on the destination image formation and the participants also perceived the importance or' these attributes differently. The findings also provided implications for event planners and other MICE stakeholders in Jordan as well as for academic researchers in MICE tourism.